DEVELOPMENT OF SELF ADAPTATION GUIDANCE FOR SMK PRAKERIN STUDENT - Latifah, Leny (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
Self adaptation is individual skill to react effectively in social connection environment individual in a place. The training guidance self adaptation in prakerin is developed for make counselor easier in the school for give service optimally and prepares students well before prakerin. Research subject is 11 grade of SMK PGRI Pakisaji Malang. The purpose of the research is produce training project self adaptation SMK student in prakerin place. Test effectiveness is done with one group pre-test post test planning. The instrument which is used is self project scale in prakerin with grain validity ≥ 0,3 and reliability alpha Cronbach 0,882. The result of the research show that (1) the project that is developed has complete acceptability and, (2) it has improve of effectively self adaptation SMK student in prakerin place.